2016
DOI: 10.1159/000448112
|View full text |Cite
|
Sign up to set email alerts
|

BRAF<sup>V600E</sup> Mutation: Has It a Role in Cervical Lymph Node Metastasis of Papillary Thyroid Cancer?

Abstract: Background: The BRAFV600E mutation is common in papillary thyroid cancer (PTC). Lymph node metastasis (LNM) may be associated with poor prognosis. However, the LNM mechanism remains unclear. Objectives: Our aim was to evaluate the prevalence of the BRAFV600E mutation in primary tumors and accompanying LNM at the time of diagnosis. Methods: This retrospective study included 51 PTC patients (40 women, 11 men; mean age 40.0 ± 16.5 years; range 6-81) who underwent total thyroidectomy accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…No researchers have yet analyzed the association between cervical LNM and CNB-T in thyroid cancer, so it remains unclear whether CNB-T is superior to FNAB-C in indicating LNM. In addition, the BRAF V600E mutation is the most common genetic alteration in thyroid cancer and occurs in nearly 80% of primary tumors and 50% of metastatic lymph nodes (22,23). It therefore remains unknown whether the introduction of BRAF V600E mutation assessment could increase the diagnostic reliability of CNB-T and FNAB-C.…”
Section: Introductionmentioning
confidence: 99%
“…No researchers have yet analyzed the association between cervical LNM and CNB-T in thyroid cancer, so it remains unclear whether CNB-T is superior to FNAB-C in indicating LNM. In addition, the BRAF V600E mutation is the most common genetic alteration in thyroid cancer and occurs in nearly 80% of primary tumors and 50% of metastatic lymph nodes (22,23). It therefore remains unknown whether the introduction of BRAF V600E mutation assessment could increase the diagnostic reliability of CNB-T and FNAB-C.…”
Section: Introductionmentioning
confidence: 99%
“…tumor and mutation-positive metastases were also frequently reported [13,14,34,35]. An interesting genomics study was reported by Le Pennec et al [15] who performed a systemic cDNA sequencing screening of a primary tumor (different subregions), lymph node metastases and distant (pleural) metastasis in a patient with an aggressive PTC.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, when the size of the largest metastatic focus of LNM was ≥0.65 cm, the BRAF V600E mutation frequency was lower. In contrast, Kurtulmus et al showed that BRAF V600E-positive metastatic lymph nodes were greater in diameter than those without the BRAF V600E mutation ( 10 ). Different results may be due to the remarkably lower overall BRAF V600E positivity in LNM in their study (47.1%, 24/51) compared with our study (78.0%, 291/373) and other studies (73.9, 81.0%) ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some scientists hope that we may extend our observation to metastatic PTC to generate a critical mass of data for clinical practice ( 8 ). However, only a few studies have examined BRAF V600E mutation in metastases, such as lymph node metastasis (LNM) ( 9 , 10 ). The PTC prognosis is usually favorable with appropriate treatment, however, LNM can develop during early stages of the disease ( 11 ).…”
Section: Introductionmentioning
confidence: 99%